The Space of Dirac-Minimal Metrics is Connected in Dimensions 2 and 4 - Ammann, Bernd; Dahl, Mattias (Symmetry, Integrability and Geometry: Methods and Applications, 2025)
Let be a closed connected spin manifold. Index theory provides a topological lower bound on the dimension of the kernel of the Dirac operator, which depends on the choice of Riemannian metric. Riemannian metrics for which this bound is attained are called Dirac-minimal. We show that the space of Dirac-minimal metrics on is connected if is of dimension 2 or 4.